The doctor's reunion to remember - Claydon, Annie (Reunited at St Barnabas's Hospital, 2021)
"A forgotten past...an unforgettable future? Former workaholic Dr. Gil Alexander is happy with the slower-paced life he was forced to adopt following his traumatic brain injury. The only things missing are his memories of just before the accident. But when Dr. Clemmie Francis is temporarily assigned to his rehabilitation center, he can't shake the feeling he's met this captivating yet cautious doctor before...and that this isn't the first time he's experienced their explosive chemistry!" --